Update on the drug treatment of hypertension: perspectives in clinical pharmacology - Le, Chuyen; Nguyen, Thi Lan Nhi; Do, Thi Hong Diep; Nguyen, Thanh Tin; Nguyen, Le Hong Van (Tạp chí Y Dược Huế, 2022)
Drug therapy to achieve the recommended target blood pressure remains the cornerstone of the management of hypertension. Today, there are strong evidences from randomized controlled trials that antihypertensive drugs are more effective than placebo at reducing cardiovascular mortality and morbidity. According to more recent guidelines, there are three main classes of drugs that have been used for initial monotherapy: inhibitors of the renin-angiotensin system, calcium channel antagonists, and diuretics. The use of beta blockers has been restricted for initial monotherapy in the absence of a specific indication associated with adverse effects on some outcomes, particularly in older patients. Many studies have demonstrated that antihypertensive agent classes can be combined effectively and nowadays, it is strongly recommended to use single-pill combinations containing two or three antihypertensive agents. Combination therapy provides greater antihypertensive potential, reduced risks for side effects, lower medical cost, increase compliance, and promotes long-term adherence, this latter being the major challenge of drug therapy for hypertension.